The arbitration of financial disputes: the commercial arbitration act 1985 (WA) - Evans, Philip (School of Business Law, Curtin Business School, Curtin University of Technology, 2009)
The Commercial Arbitration Act 1985 (WA) provides a rapid and cost effective method for the resolution of commercial disputes. Although essentially adversarial, the flexibility of the process allows the procedures to be modified to suit the particular dispute. The act states that the arbitrator is not bound by the rules of evidence, and pleadings normally required in litigation need not apply. At the same time there is certainty in the outcome in that there are limited grounds for the appeal of an arbitrator's determination. The ambit of an arbitrator's jurisdiction is relevant to the finance industry as it can extend to resolution of disputes arising from contractual breaches, negligence, trade practices and breaches of the consumer protection provisions of the Australian Securities and Investment Commission Act 2001 (Cth). Hearings are held in private and the specialist expertise of the arbitrator greatly assists in the speedy resolution of the dispute. This article discusses the provisions and application of the Commercial Arbitration Act to commercial disputes.